Analysis of students' ecoliteracy at Adiwiyata school in Padang City - Sari, Rona Taula; Syukmanetti, Syukmanetti; Anggreni, Siska; Nora, Yulfia; Jusar, Ira Rahmayuni; Rosabela, Fitriani; Hisfiani, Anisa (Universitas Wiralodra, 2025)
The implementation of the Adiwiyata program is expected to enhance students' awareness and understanding of environmental issues, fostering a strong sense of ecoliteracy. However, based on the facts in the field, the existence of the Adiwiyata program has not been able to guarantee an increase in environmental awareness among students. This study aims to analyze the implementation of the Adiwiyata program in fostering and developing student ecoliteracy. This study is a descriptive research employing quantitative methods, aimed at objectively describing and analyzing existing phenomena or conditions related to the implementation of the Adiwiyata program and its impact on student ecoliteracy. In collecting data, researchers used a questionnaire completed directly by junior high school students participating in the Adiwiyata program, involving 101 students from six schools. The data collected from respondents were analyzed using quantitative descriptive analysis techniques. This study shows that students in Adiwiyata schools show a level of ecoliteracy in the sufficient category. This is due to various factors, one of which is that the implementation of the Adiwiyata program in junior high schools in Padang City is still relatively voluntary and independent. Support from all stakeholders, including the education office and local communities, is necessary to ensure that the Adiwiyata program is not only symbolic but also truly creates a sustainable ecoliteracy transformation.